SARS-CoV-2 variants of concern surveillance including Omicron using RT-PCR–based genotyping offers comparable performance to whole genome sequencing - Vanoni, Simone; Matulevicius, Arnoldas; Avdiu, Besard; Scantamburlo, Giada; Ulekleiv, Camilla; Brzoska, Pius M.; Furtado, Manohar R.; Feenstra, Jelena D. M.; Rico, Alain; Gandhi, Manoj; Giacobazzi, Elisabetta; Masi, Elisa; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Known SARS-CoV-2 variants of concern (VOCs) can be detected and differentiated using an RT-PCR–based genotyping approach, which offers quicker time to result, lower cost, higher flexibility, and use of the same laboratory instrumentation for detection of SARS-CoV-2 when compared with whole genome sequencing (WGS). In the current study, we demonstrate how we applied a genotyping approach for identification of all VOCs and that such technique can offer comparable performance to WGS for identification of known SARS-CoV-2 VOCs, including more recent strains, Omicron BA.1 and BA.2.